Avaliação histológica da biocompatibilidade do polímero da mamona no dorso nasal de macacos-pregos (Cebus apella) - De Jesus Dias, Paulo Cesar; Granato, Lidio; De Oliveira Ramalho, Lizeti De Toledo [UNESP]; De Oliveira, José Américo [UNESP]; Pretel, Hermes [UNESP] (Elsevier, 2009)
Bone tissue lesions can be caused by congenital and acquired factors, and result in nasal deformities with cosmetic and functional repercussion. Surgical treatment in these cases frequently requires complex reconstructions and the use of biomaterials. The polyurethane derived from castor beans (Ricinus communis) has a favorable formulation in terms of ease of processing, flexibility, no emission of toxic vapors and low cost. Nonetheless, despite favorable results, studies about the use of castor beam polymer (Ricinus communis) assessing tissue reaction on the nasal dorsum are still missing in the literature. Aim: the goal of the present investigation is to histologically assess the Ricinus communis polymer implant biocompatibility with the nasal dorsum. Study design: experimental. Materials and Methods: we used four Cebus appela monkeys, in which we created a nasal dorsal defect in all the animals and there we placed the aforementioned implant. The animals were sacrificed 270 days after surgery and the samples were submitted to histological study. Results: in the histology analysis we did not observe the presence of foreign body granulomas or phagocytic cells. We also observed a progressive bone formation and maturation. Conclusion: macroscopic and microscopic results showed that the castor oil polymer implant was biocompatible. © Revista Brasileira de Otorrinolaringologia.
Ricinus communis biocompatibility histological study in the nose of Cebus apella monkeys
Keywords: Biocompatible materials; Castor bean; Nose; Polymers